Electrochemical stability of RuO2(110)/Ru(0001) model electrodes in the oxygen and chlorine evolution reactions. (10th March 2020) - Goryachev, Andrey; Etzi Coller Pascuzzi, Marco; Carlà, Francesco; Weber, Tim; Over, Herbert; Hensen, Emiel J.M.; Hofmann, Jan P.
Abstract: RuO2 is commercially employed as an anodic catalyst in the chlor-alkali process. It is also one of the most active electrocatalysts for the oxidation of water, relevant to electrochemical water splitting. However, the use of RuO2 is limited by its low anodic stability under acidic conditions, especially at high overpotentials. In the present work, the electrochemical stability of model RuO2 (110)/Ru(0001) anodes was investigated in order to gain a deeper understanding of the relation between structure and performance in Cl2 and O2 evolution reactions (CER and OER, respectively). Online electrochemical mass spectrometry was used to determine the onset potential of CER and OER in HCl and H2 SO4 electrolytes, respectively. The onset potential of OER was higher in HCl than in H2 SO4 due to competition with the kinetically more favorable CER. A detailed stability evaluation revealed pitting corrosion of the electrode surface with exposure of Ru(0001) metal substrate concomitant with the formation of a hydrous RuO2 in some areas regardless of the applied electrochemical treatment. However, despite local pitting, the RuO2 (110) layer preserves its thickness in most areas. Degradation of the electrode was found to be less severe in 0.5 M HCl due to a decrease in the faradaic efficiency of RuO2 oxidation caused by competition with the kinetically more favorable CER. Highlights: Pitting corrosion occurs during O2 and Cl2 evolution on the surface of RuO2 (110)/Ru(0001). Electrochemical growth of hydrous RuO2 in the pits by oxidation of Ru 0 substrate. RuO2 (110) layers, where not removed by pitting, remain intact. Corrosion onsets determined by on-line electrochemical mass spectrometry. OER led to higher corrosion than CER at same potential.